Burkholdaeria Cepacia Infection In Immunocompetent Children: A Clinical Analysis Of 20 Cases - Chinmoyee Ray, Priyabhasini; Panda, Suchismita; Mishra, Soumya; Dash, Dillip Kumar; Mohanty, Mamta Devi; Saboth, Prasant Kumar; Sarath, P Sai; Patra, Chandra Sekhar (Journal of Neonatal Surgery, 2025)
Background: Burkholderia cepacia is an emerging opportunistic pathogen causing nosocomial infection in pediatric patient having cystic fibrosis and other underlying disease condition causing immunodeficiency. The clinical diagnosis and treatment of B. cepacian infection remains poorly studied. Burkholderia cepacia complex (Bcc) is a Gram-negative, oxidase-positive, non-fermenting saprophytic bacilli, belonging to the Burkholderiaceae family comprising twenty taxonomically valid species. Bcc is a devastating pulmonary pathogen in cystic fibrosis patient and has also been reported with increasing frequency as a cause of bacteremia, particularly in patients with indwelling catheters, urinary tract infection and peritonitis. This study will analyze the risk factors, antimicrobial sensitivity pattern, and clinicopathological spectrum of Burkholderia cepacia infection, aiming to improve the treatment of B. cepacia infection. Unlike other studies, we are studying B. Cepacia infection in immunocompetent children, as most of the patients were admitted for Lower respiratory tract infection and other infection without any chronic disease and immunodeficiency. Objectives: Primary - To Analyze the clinical spectrum of Immuno-competent patients infected by B. cepacian. Methods: This study has been approved by Institution and Ethics Committee (IEC) of IMS and SUM Hospital. In this retrospective analytical study based on the 20 cases of infection caused by B.cepacia in children (1 month to 14 years) without Immuno-deficiency, who were admitted in IMS and SUM Hospital since Past 6 Months showing any Culture (B.cepacia ) Positive were included .Children having any underlying Immunodeficiency, Chronic Liver Disease and Chronic Kidney Disease were excluded. Conclusion: B.Cepacia generally causes opportunistic infection in immuno- compromised children unlike our study which shows infection in immuno-competent children as well. A multi drug resistance is a challenging issue in such type of infections. Therefore, a high index of suspicion is required to monitor B.Cepacia infection and early institution of appropriate antimicrobial therapy.